2020
DOI: 10.18632/aging.102721
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of miR-96-5p by catalpol ameliorates oxidative stress and hepatic steatosis in LDLr-/- mice via p66shc/cytochrome C cascade

Abstract: Hepatic steatosis and oxidative stress are considered to be the sequential steps in the development of nonalcoholic fatty liver disease (NAFLD). We previously found that catalpol, an iridoid glucoside extracted from the root of Romania glutinosa L, protected against diabetes-induced hepatic oxidative stress. Here, we found that the increased expression of p66shc was observed in NAFLD models and catalpol could inhibit p66shc expression to ameliorate NAFLD effectively. However, the underlying mechanisms remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Cheng et al demonstrated that miR-421 overexpression significantly decreased hepatic MnSOD and CAT expression and subsequently aggravated oxidative damage upon NAFLD stimulation via directly targeting sirtuin 3 [ 53 ]. In addition, Zhang et al recently showed that miR-96-5p was capable of suppressing p66shc expression, thereby reducing oxidative stress and hepatic steatosis [ 54 ]. Based on these contexts, we thus investigated the function of miR-137-3p, a potential antioxidant molecule in the liver, during NAFLD progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al demonstrated that miR-421 overexpression significantly decreased hepatic MnSOD and CAT expression and subsequently aggravated oxidative damage upon NAFLD stimulation via directly targeting sirtuin 3 [ 53 ]. In addition, Zhang et al recently showed that miR-96-5p was capable of suppressing p66shc expression, thereby reducing oxidative stress and hepatic steatosis [ 54 ]. Based on these contexts, we thus investigated the function of miR-137-3p, a potential antioxidant molecule in the liver, during NAFLD progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome C participates in ROS production and mitochondrial apoptosis. Zhang et al found that the upregulation of miR-96-5p ameliorated NAFLD through inhibition of the p66shc/cytochrome C cascade [78]. The brief information of the above-mentioned miRNAs has been summarized in Table 3.…”
Section: The Role Of Mirnas In Modulation Of Oxidative Stress and Er Stress In Nafldmentioning
confidence: 99%
“…Catalpol is an iridoid glucoside derived from Rehmannia glutinosa that exerts anti-cancer, neuroprotective, anti-inflammatory, antioxidant stress, and mitochondrial function regulatory effects (Jiang and Zhang, 2020;Yan et al, 2020;Zhang et al, 2020). CTL can inhibit H 2 O 2 -induced cardiomyocyte apoptosis through the mitochondria-dependent caspase pathway.…”
Section: Catalpol (Ctl)mentioning
confidence: 99%